THE ROLE OF BAWASLU IN ENSURING FAIR AND HONEST REGIONAL ELECTIONS IN PASAMAN REGENCY UNDER INDONESIA'S ELECTION LAW NO. 7 OF 2017 - Yunis, Aldi; Pertiwi, Dian; Fitri, Hidayati; Husni, Alfi (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
This study examines two main issues: the authority of Bawaslu in supervising the implementation of honest and fair regional head elections in Pasaman Regency and the perspective of siyasah tanfidziyah regarding Bawaslu's role in these elections. The research aims to analyze Bawaslu's supervisory authority over regional head elections in Pasaman Regency and explore the views of siyasah tanfidziyah on its role in ensuring fair and honest elections.  The research adopts an empirical juridical approach, focusing on the operations of Bawaslu in Pasaman Regency. Primary data were collected from the Pasaman Regency General Election Supervisory Agency (Bawaslu) and community figures, while secondary data were obtained from legal documents, regulations, books, and journals. Data collection methods included interviews and documentation. The analysis utilized descriptive techniques to evaluate Bawaslu's authority in ensuring fair elections in Pasaman Regency, grounded in the provisions of Law Number 7 of 2017.The findings indicate that Bawaslu in Pasaman Regency has fulfilled its duties and exercised its authority as mandated by Law Number 7 of 2017. However, limited public awareness of election violation reporting procedures presents a significant challenge for Bawaslu in addressing such cases. This highlights the need for Bawaslu to actively promote public awareness through educational and outreach programs that engage the community directly. Enhanced public participation in reporting violations would improve Bawaslu’s effectiveness in fulfilling its supervisory functions.From the perspective of fiqh siyasah, Bawaslu functions as part of al-shulthah tanfidziyah, carrying out its mandate to oversee and enforce election laws. This aligns with its executive role in maintaining order and fairness during elections, ensuring compliance with democratic principles.